(untitled) (REMUNOM, 2025)
This study conducted an environmental diagnosis at the Institute of Higher Education (IES) to identify environmental aspects and impacts, aiming to propose sustainable practices. The methodology involved the Environmental Aspects and Impacts Assessment (LAIA), including technical visits, interviews, and literature review, analyzing activities in blocks A, B, C, D, and E. Significant impacts were identified, such as high energy and water consumption, generation of solid, chemical, and biological waste, and greenhouse gas emissions. The LAIA matrix classified impacts by severity and frequency, highlighting the need for measures like energy efficiency, waste management, and rational water use. The Environmental Agenda in Public Administration (A3P) served as a reference, evaluating seven axes: rational resource use, waste management, quality of life, training, sustainable procurement, environmental integration, and sustainable construction. IES shows progress, such as proper disposal of hazardous waste and sustainable procurement, but lacks monitoring of energy, water, and paper consumption, as well as a construction waste management plan. Proposed goals include awareness campaigns, document digitalization, composting, and sustainable construction. Measurable indicators were defined to track progress. The research concludes that implementing an efficient Environmental Management System can reduce impacts, promoting environmental, economic, and social benefits, with an emphasis on raising awareness in the academic community.